2019
DOI: 10.1371/journal.pone.0223472
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical effects of MitraClip on leaflet stress and myocardial strain in functional mitral regurgitation – A finite element modeling study

Abstract: PurposeMitraClip is the sole percutaneous device approved for functional mitral regurgitation (MR; FMR) but MR recurs in over one third of patients. As device-induced mechanical effects are a potential cause for MR recurrence, we tested the hypothesis that MitraClip increases leaflet stress and procedure-related strain in sub-valvular left ventricular (LV) myocardium in FMR associated with coronary disease (FMR-CAD).MethodsSimulations were performed using finite element models of the LV + mitral valve based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…While exact causality for MR recurrence cannot be discerned from our current results, it is also possible that MitraClip induced annular remodeling alters valve coaptation geometry, augments angular displacement between the mitral valves and sub-valvular apparatus, and/or induces myocardial tethering – each of which can contribute to MR. Consistent with the latter, recent computational modeling data from our group demonstrated that MitraClip augmented leaflet stress immediately adjacent to the device as well as LV myocardial stretch adjacent to the mitral annulus: [8] Our current results provide proof of concept that device-induced annular remodeling occurs in vivo, severity of which can be discerned on 3D TEE as a means of predicting therapeutic response to MitraClip. Whereas a large majority (70/80) of our study population underwent repair using the MitraClip NT/NTr device, our finding of an impact of MitraClip on annular remodeling is of relevance in context of new modifications of the device (XTr) that grasp a wider amount of leaflet tissue, and would thus be expected to apply a greater magnitude of force on the mitral annulus.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While exact causality for MR recurrence cannot be discerned from our current results, it is also possible that MitraClip induced annular remodeling alters valve coaptation geometry, augments angular displacement between the mitral valves and sub-valvular apparatus, and/or induces myocardial tethering – each of which can contribute to MR. Consistent with the latter, recent computational modeling data from our group demonstrated that MitraClip augmented leaflet stress immediately adjacent to the device as well as LV myocardial stretch adjacent to the mitral annulus: [8] Our current results provide proof of concept that device-induced annular remodeling occurs in vivo, severity of which can be discerned on 3D TEE as a means of predicting therapeutic response to MitraClip. Whereas a large majority (70/80) of our study population underwent repair using the MitraClip NT/NTr device, our finding of an impact of MitraClip on annular remodeling is of relevance in context of new modifications of the device (XTr) that grasp a wider amount of leaflet tissue, and would thus be expected to apply a greater magnitude of force on the mitral annulus.…”
Section: Discussionsupporting
confidence: 85%
“…MitraClip induced leaflet tension may alter annular geometry – thus contributing to recurrent MR via distortion of valve coaptation and tethering of peri-annular myocardium. Consistent with this, computational modeling studies have shown MitraClip to augment leaflet stress adjacent to the device and also to affect broader aspects of the mitral apparatus - including decreased annular size and increased stretch (displacement) of peri-annular LV myocardium [8]. It remains unclear whether clinical application of MitraClip produces in vivo alterations in mitral annular geometry, and how such remodeling impacts patient outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…The implantation of Mitraclip has mechanical effects including an increase in mitral leaflet stress and sub‐valvular radial strain proportional to the increase in the left ventricular chamber size as shown in an animal study with functional MR 12 . Since functional MR, secondary to left ventricular and annular dilatation and papillary muscle displacement, is commonly a result of CAD/acute coronary syndrome, this increased stress in already vulnerable myocardium could lead to worse postprocedural outcomes partially because of higher severity of residual MR and a higher risk of recurrence of severe MR 12 …”
Section: Discussionmentioning
confidence: 99%
“…The MitraClip™ (Abbott, Santa Clara) is currently the sole percutaneous device that is commercially approved to treat functional mitral regurgitation and more than 80,000 patients have undergone repair with this device in the past decade ( Abbott 2019 ). To reduce regurgitation, the device approximates the anterior and posterior mitral valve leaflets to create a double-barrel mitral orifice, a process that is relatively straightforward to simulate in a finite element setting ( Zhang et al 2019 ). The process to assess credibility of these simulations can be classified into three categories: First, the approach should show a general agreement between the expected behavior and the predicted metrics.…”
Section: Regulatory Perspective—medical Device Innovationmentioning
confidence: 99%
“…An important missing link is the longitudinal assessment of chronic disease management. From an analysis point of view, this involves not only simulate and analyze the acute changes in the stretch and stress profiles in response to the intervention ( Zhang et al 2019 ), but to predict and understand the chronic changes in form and function ( Rausch et al 2017 ). Another future direction is to integrate simulation results, animal models, and clinical data using physics-based machine learning towards a more holistic understanding of disease progression and the long-term effects of intervention.…”
Section: Regulatory Perspective—medical Device Innovationmentioning
confidence: 99%